EXPLORING THE IMPACT OF ANGLE BISECTORS IN OPTIMUM SENSOR PLACEMENT FOR ENVIRONMENTAL MONITORING - Norova Gulrukh (Web of Journals Publishing, 2025)
When solving geometric difficulties, such as where to put sensors to monitor the environment, angle bisectors come in handy. In this work, we investigate the characteristics of angle bisectors and their use in figuring out where to put sensors in an environmental monitoring network most effectively. Our goal is to create a technique for strategically placing sensors to optimize coverage and efficiency in monitoring environmental factors, utilizing the angle bisector theorem and other geometric concepts. The findings of this study have the potential to increase the accuracy of data gathering, lower expenses, and boost the general efficacy of environmental monitoring systems.
Keywords: Properties of angle bisectors, angle, triangle, angle bisectors, geometric principle.